2022
DOI: 10.3389/fgene.2022.953580
|View full text |Cite
|
Sign up to set email alerts
|

MiR-33a targets FOSL1 and EN2 as a clinical prognostic marker for sarcopenia by glioma

Abstract: To determine the relationship between glioma and muscle aging and to predict prognosis by screening for co-expressed genes, this study examined the relationship between glioma and sarcopenia. The study identified eight co-downregulated miRNAs, three co-upregulated miRNAs, and seven genes associated with overall glioma survival, namely, KRAS, IFNB1, ALCAM, ERBB2, STAT3, FOSL1, and EN2. With a multi-factor Cox regression model incorporating FOSL1 and EN2, we obtained ROC curves of 0.702 and 0.709, respectively, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 75 publications
0
4
0
Order By: Relevance
“…Increased copy number and mRNA overexpression of FOSL1 gene are frequently observed in primary breast cancers, independently and irrespectively of the patients’ lymph node axillary metastatic status [ 55 ]. Analysis from transcriptomic FPKM expression data obtained from UCSC Xeba website ( https://xenabrower.net/ ) by Jin’s group demonstrated that FOSL1 can better predict glioma prognosis [ 56 ]. Our previous bioinformatic analysis from TCGA mRNA data showed that FOSL1 serves as a diagnostic and prognostic marker for glioma patients [ 6 ].…”
Section: Discussionmentioning
confidence: 99%
“…Increased copy number and mRNA overexpression of FOSL1 gene are frequently observed in primary breast cancers, independently and irrespectively of the patients’ lymph node axillary metastatic status [ 55 ]. Analysis from transcriptomic FPKM expression data obtained from UCSC Xeba website ( https://xenabrower.net/ ) by Jin’s group demonstrated that FOSL1 can better predict glioma prognosis [ 56 ]. Our previous bioinformatic analysis from TCGA mRNA data showed that FOSL1 serves as a diagnostic and prognostic marker for glioma patients [ 6 ].…”
Section: Discussionmentioning
confidence: 99%
“…Hence, there is potential for miR-455-3p and miR-434-3p to serve as a biomarker for both CHF and sarcopenia. Wang and others investigated the connection between glioma and muscle aging with the goal of glioma prognosis using co-expressed genes ( Wang et al, 2022 ). They discovered seven survival-related genes, including FOSL1, KRAS, STAT3, ALCAM, ERBB2, IFNB1, and EN2, as well as eight co-downregulated miRNAs, three co-upregulated miRNAs, and three co-regulated miRNAs.…”
Section: Regulatory Mechanisms Of Non-coding Rnas In Muscle Agingmentioning
confidence: 99%
“…Even when EGFR and MET were inhibited, the suppression of FOSL1 phosphorylation was temporary, rebounding within 48 h. Consequently, the rebound led to increased transcription levels of five FOSL1 target genes, namely SPRY2, MMP2, JUN, PLAUR, MMP1, and IL-6, contributing to resistance against kinase inhibitors [48][49][50][51][52][53][54]. FOSL1 serves as a clinical prognostic marker for glioma [21,26,55].…”
Section: The General Roles Of Fosl1 In Glioma and Other Tumor Typesmentioning
confidence: 99%